Intelligent Control System Determinations Of Carbon Oxide Concentration In Biogas (Texas Journal of Engineering and Technology, 2024)
This article discusses the development and implementation of an automated system for determining the concentration of carbon monoxide (CO). The level of carbon monoxide plays a significant role in the sale of biogas. Therefore, accurate and reliable determination of its concentration is an important aspect in monitoring and ensuring environmental safety. The article describes the operating principle of the developed system, including the selection of sensors, measurement techniques, and automated processes for data collection and analysis. An algorithm for data processing and presentation of results is also discussed, which provides operators and researchers with easy access to information on CO concentrations